INOVASI PROGRAM ELECTRONIC TRAFFIC LAW ENFORCEMENT (E-TLE) DI KOTA SURABAYA. - Ika Devi Lestari; Ditasari Wardani; Sri Wibawani (Jurnal Penelitian Administrasi Publik, 2020)
Police Departement of Surabaya City and Surabaya City Government collaborated in the procurement and installation of CCTV (Camera Closed Circuit Television) robots at several red light points for traffic law enforcement purposes. The collaboration is in the form of an innovative development of the Electronic Traffic Law Enforcement (E-TLE) ticketing method as a service for Traffic Police Unit (SATLANTAS) and for road users. E-TLE is one of the methods in the Electronic Traffic Ticket system (E-Tilang). In addition to the hunting system and stationary system methods used, there is an effort to improve the performance of services performed by traffic police officers, so that this study aims to analyze the E-TLE Innovation in Surabaya. This research was conducted at Police Departement of Surabaya City and Surabaya City Transportation Department using qualitative methods and descriptive approaches, and data obtained from documents, interviews at the Traffic Police Unit (SATLANTAS) and Surabaya City Transportation Department. The analysis of this study uses Roger's Theory by looking at: (1) Relative Advantages; (2) Compatibility; (3) Complexity; (4) Triability; and (5) Observability. The results showed that this innovation can reduce the number of traffic violations, avoiding the practice of flirting between officers and violators directly in the City of Surabaya. Keywords: Inovation;Tilang; Electronic Traffic Law Enforcement (E-TLE); Police Departement of Surabaya City.